Peran Perpustakaan Madrasah dalam Mendukung Program Moderasi Beragama di MTsS Ulumul Quran Banda Aceh - Nabila, Risma; Rasyid, Saiffuddin A.; Safri, T. Mulkan; Manan, Abdul; Ali Hasan, Nurhayati (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This study aims to determine the role of the MTsS Ulumul Quran library in supporting the religious moderation program and the strategies used by the MTsS Ulumul Quran library in implementing the religious moderation program among madrasahs. Based on data found in the field, the MTsS Ulumul Quran library together with teachers have made efforts to increase awareness and understanding of students about religious moderation, provide a religious moderation reading corner, and expand access to digital information. The method used in this study is qualitative with a descriptive approach. Data collection was obtained through observation, interviews and documentation. The subject in this study was a librarian who was selected using the purposive sampling technique. The results of the study indicate that the role of the MTsS Ulumul Quran library in implementing the religious moderation as the followings: as the main source of teaching and learning activities, developing reading interests and habits, a strategic place to find information, a place to establish communication between users, as an agent of change, builder, and preservation of culture, and the level of community progress. This study also revealed several obstacles faced by the library, namely limited collections, difficulty in attracting students' interest in reading, and lack of discussion space in the library. The implementation of the